Quasiparticle diffusion and edge losses in superconducting tunnel junction detectors with two active electrodes - Parlato, L; Ammendola, G; Cristiano, R; Esposito, E; Frunzio, L; Kraus, H; Lisitskii, M; Nappi, C; Pagano, S; Peluso, G; Pepe, G; Valko, P; et al. (Elsevier, 2000)
A theoretical model to describe the spectral response of SIS tunnel junctions under irradiation in the presence of diffusion and edge losses of non-equilibrium quasiparticles has been developed. The model takes into account the back-tunnelling effect, in the general case of asymmetrical rates of tunnelling, γ12≠γ21. It provides a quantitative estimate of parameters like the edge reflectivity, the diffusion length and the diffusion coefficient, which are important parameters for a diagnostic of STJ-detectors. The predictions of the theory are compared with an experimental spectrum obtained from a Nb-based STJ.